De-escalation Techniques for students with Emotional and Behavioral Disorders - Hawkinson, Tara (My University, 2012)
This study proposes to look for a relationship between the de-escalation techniques and the amount and severity of aggressive behaviors in students who have an Emotional/Behavioral Disorder. The Crisis Prevention intervention teaches strategies that may help provide students with EBD the ability to de-escalate situations so they can function in the regular education setting with their peers and later on to function within society as adults. To implement this study each time a student got referred to the EBD room for a behavioral issue the special education teacher implemented CPI?s strategies to help the student de-escalate his/her behavior. The teacher recorded the amount of time it took for the student to de-escalate inappropriate behaviors and the level of aggressiveness that the behavior had escalated too. When the student was ready to self-compose, accept responsibility for behaviors, and the student accepted and followed through on the consequences for behaviors the student went back to the mainstream setting. Results of this study indicated that there is a highly significant correlation between the Crisis Prevention Intervention strategies that were implemented and a decrease in time spent in the EBD room and time spent at a crisis level.
Keywords: behavioral disorder; Special Education; emotional disorder; EBD; Educational Leadership; de-escalation techniques; crisis prevention intervention